COLOR COMBINATION IN INTERIOR AND EXTERIOR DECORATION: आंतरिक एवं बाह्रय सज्जा में रंग संयोजन - Sharma, Krishna (International Journal of Research -GRANTHAALAYAH, 2014)
"Color is a quality of light" that the eyes see. Colors are closely related to human life. Every beautiful thing affects a man's heart and emotions. Colors have the same importance in decoration as salt in food. Just as the food fades without salt, similarly the imagination of the interior and exterior of the house without colors is meaningless. The effect of colors can enlarge, shrink, heat, and cool the room. Color can create a dull atmosphere, making simple decorations look gorgeous. ‘‘रंग प्रकाश का एक गुण है’’ जिन्हें आंखे देखती हैं। रंगों का मानव जीवन से घनिष्ठ सम्बंध है। प्रत्येक सुंदर वस्तु मनुष्य के ह्रदय और भावनाओं को प्रभावित करती है। सजावट में रंगों का वही महत्व है जो भोजन में नमक का। जिस तरह बगैर नमक के भोजन फीका हो जाता है उसी तरह बगैर रंगों के घर की आंतरिक एवं बाह्रय सज्जा की कल्पना ही व्यर्थ है। रंगों का प्रभाव कमरे को बड़ा कर सकता है, छोटा कर सकता है, गरम कर सकता है ठंडा कर सकता है। रंग नीरस वातावरण को उल्लासमय बना सकता है, साधारण सजावट को भव्य बना सकता है।